A template for physical resilience research in older adults: Methods of the PRIME‐KNEE study. Issue 11 (29th July 2021) - Whitson, Heather E.; Crabtree, Donna; Pieper, Carl F.; Ha, Christine; Au, Sandra; Berger, Miles; Cohen, Harvey J.; Feld, Jody; Smith, Patrick; Hall, Katherine; Parker, Daniel; Kraus, Virginia Byers; et al.
Abstract: Background: Older adults with similar health conditions often experience widely divergent outcomes following health stressors. Variable recovery after a health stressor may be due in part to differences in biological mechanisms at the molecular, cellular, or system level, that are elicited in response to stressors. We describe the PRIME‐KNEE study as an example of ongoing research to validate provocative clinical tests and biomarkers that predict resilience to specific health stressors. Methods: PRIME‐KNEE is an ongoing, prospective cohort study that will enroll 250 adults ≥60 years undergoing total knee arthroplasty. Data are collected at baseline (pre‐surgery), during surgery, daily for 7 days after surgery, and at 1, 2, 4, and 6 months post‐surgery. Provocative tests include a cognition‐motor dual‐task walking test, cerebrovascular reactivity assessed by functional near‐infrared spectroscopy, peripheral blood mononuclear cell reactivity ex vivo to lipopolysaccharide toxin and influenza vaccine, and heart rate variability during surgery. Cognitive, psychological, and physical performance batteries are collected at baseline to estimate prestressor reserve. Demographics, medications, comorbidities, and stressor characteristics are abstracted from the electronic medical record and via participant interview. Blood‐based biomarkers are collected at baseline and postoperative day 1. Repeated measures after surgery include items from a delirium assessment tool and pain scales administered daily by telephone for 7 days and cognitive change index (participant and informant), lower extremity activities of daily living, pain scales, and step counts assessed by Garmin actigraphy at 1, 2, 4, and 6 months after surgery. Statistical models use these measures to characterize resilience phenotypes and evaluate prestressor clinical indicators associated with poststressor resilience. Conclusion: If PRIME‐KNEE validates feasible clinical tests and biomarkers that predict recovery trajectories in older surgical patients, these tools may inform surgical decision‐making, guide pre‐habilitation efforts, and elucidate mechanisms underlying resilience. This study design could motivate future geriatric research on resilience.